Determination of the surface thermodynamic characteristics and the structural isomer separation ability of new synthesized phenylbenzoate-based three-ring calamitic liquid crystals by inverse gas chromatography - Cakar, Ayse Erdogan; Cakar, Fatih; Ocak, Hale; Karavelioglu, Selvi; Eran, Belkiz Bilgin; Cankurtaran, Ozlem (ELSEVIER, 2022)
Two different new calamitic liquid crystals (LCs), (4-[4-((S)-3,7-dimethyloctyloxy)phenoxy)carbonyl]phenyl 4-(n-decyloxy)benzoate (DPDEB) and 4-[4-((S)-3,7-dimethyloctyloxy)phenoxy)carbonyl]phenyl 4-(n-dodecyloxy)benzoate (DPDOB)) were synthesized and characterized using H-1-NMR, and C-13-NMR. The LC behavior of the target compounds was investigated by optical polarization microscopy (PM) and differential scanning calorimetry (DSC). The selectivity coefficients, a, of the structural isomers at infinite dilution for the DPDEB and DPDOB LCs were determined for butyl acetate, butyl alcohol and amyl alcohol isomers. Surface energy analysis has been performed using inverse gas chromatography (IGC). By using suitable solvents, the surface properties and separation power of isomers of DPDEB and DPDOB LCs were determined between 303.2 and 323.2 K. Experiments with LC's have been conducted at infinite dilution to the specific adsorption enthalpy and the specific adsorption free energy. IGC measurements exhibited values of acidity constants (K-A) of 0.033 and 0.057 and basic constants (K-D) of 0.176 and 0.242 for DPDEB and DPDOB, respectively. It has been found that all LCs show basic character. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Inverse gas chromatography; Liquid crystal; Surface energy; Acid-base interactions; Isomer separation; ADSORPTION; BEHAVIOR; Chemistry